Other possible voices and aesthetics: ingressive, oral and manual (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article aims to list, analyze and explore vocal possibilities in performance from experiences, bibliographic, audiovisual references and historical and cultural occurrences of these techniques. Three modes of sound production from the human body were listed with scarce academic material available in Portuguese, these being, ingressive phonations, mouth sounds and manual flatus. Didactic and artistic-performance videos were also produced during the research using the techniques analyzed in order to provide other paths for the reader about the aesthetic possibilities of these sounds.
Keywords: Ingressive phonation; Mouth sounds; Manualism; Voice; Performance